Melatonin postconditioning combined with sitagliptin exerts full cardioprotection in diabetic hearts of aged rats through an AMPK-dependent mechanism - Song, Ronggang; Ren, Jing; Sun, Junxia; Li, Ming (Archives of Biological Sciences, 2021)
Paper description: Cardioprotection in diabetic elderly patients requires effective combinational therapies. This study investigated the effect of melatonin postconditioning combined with sitagliptin pretreatment on myocardial ischemia-reperfusion (IR) injury in diabetic aged rats. Combination therapy with melatonin and sitagliptin was superior to individual interventions in limiting infarct size in type-2 diabetic aged rats after IR injury as a result of suppression of mitochondrial-dependent oxidative stress and apoptosis. Cardioprotective effects of combination therapy were accomplished by activating the AMPK/SIRT1 pathway. Combined use of melatonin and sitagliptin is a potentially promising strategy for treating elderly diabetic patients with ischemic heart disease. Abstract: The presence of multiple comorbidities in patients facing myocardial ischemia-reperfusion (IR) injury is the main obstacle for cardioprotection. This study investigated the effect of melatonin postconditioning combined with sitagliptin pretreatment on cardioprotection in diabetic aged rats by evaluating oxidative stress, apoptosis and involvement of the AMPK/SIRT1 pathway. The type-2 high-fat/streptozotocin experimental model in aged Sprague-Dawley rats (n=78) was used. The animals underwent left coronary occlusion for 30 min, followed by 3 h reperfusion. Diabetic rats were pretreated with sitagliptin (20 mg/kg, i.p.) and received melatonin (10 mg/kg, i.p.) early in reperfusion. Myocardial infarct size, histological changes, oxidative markers, mitochondrial reactive oxygen species (mitoROS) and expression of proteins regulating apoptosis and AMPK/SIRT1 activity were measured. The infarct size-sparing effect of the combination of melatonin plus sitagliptin was greater than that observed in individual treatments (P<0.01). Combination therapy significantly reduced IR-induced elevation of 8-isoprostane, mitoROS and proapoptotic proteins Bax and cleaved caspase-3, and increased IR-induced downregulation of mitochondrial superoxide-dismutase, glutathione, anti-apoptotic protein Bcl2, phosphorylated AMPK and SIRT1 (P<0.01, P<0.001). Inhibition of AMPK via compound-C completely reversed combination-induced cardioprotection. Thus, improving cardiac antioxidative and antiapoptotic responses via upregulation of AMPK/SIRT1 activity may represent a central mechanism through which melatonin plus sitagliptin attenuate myocardial IR injury in diabetic-aged rats.